Parity of access to memory services in London for the BAME population: a cross-sectional study. (3rd June 2019) - Cook, Laura; Mukherjee, Sujoy; McLachlan, Tim; Shah, Rajendra; Livingston, Gill; Mukadam, Naaheed
ABSTRACT: Objective: To investigate whether referrals to memory services in London reflect the ethnic diversity of the population. Methods: Memory service data including referral rates of BAME was collected from London Clinical Commissioning Groups (CCGs). Results: The expected percentage of BAME referrals using census data was compared against White British population percentages using the chi squared test. We found that within 13, 166 referrals to memory services across London, the percentage of people from BAME groups was higher than would be expected (20.3 versus 19.4%; χ 2 = 39.203, d.f. = 1, p < 0.0001) indicating that generally people from BAME groups are accessing memory services. Seventy-nine percent of memory services had more referrals than expected or no significant difference for all BAME groups. When there were fewer referrals then expected, the largest difference in percentage for an individual ethnic group was 3.3%. Conclusions: Results are encouraging and may indicate a significant improvement in awareness of dementia and help seeking behaviour among BAME populations. Prevalence of dementia in some ethnic groups may be higher so these numbers could still indicate under-referral. Due to the data available we were unable to compare disease severity or diagnosis type.